Development of NOx Gas Sensor Based on Electrospun ZnO Nanofibers for Diagnosing Asthma Disease - Niloufar Khomarloo; Elham Mohsenzadeh; Roohollah Bagherzadeh; Masoud Latifi; Driss Lahem; Ari Hakgor; Ly Ahmadou; Hayriye Gidik (Proceedings)
Volatile organic compounds (VOCs) have the potential to serve as biomarkers for respiratory diseases such as asthma. Non-invasive respiratory analysis can be used for early detection and disease monitoring. This paper presents the development of a ZnO metal oxide nanofibers sensor as a cost-effective method for detecting NO, which is an asthma biomarker, and NO2, that can cause asthma. Electrospun metal oxide nanofibers are considered for gas sensor applications due to their unique structural and electrical properties. The results indicate that the amount of zinc acetate and the morphology of the ZnO nanofibers as a sensing medium can affect the sensitivity of the gas sensor. The preparation of electrospinning solutions containing varying amounts of zinc acetate must be carefully considered due to its impact on morphology and thus sensitivity.